Extraction of essential oil from lemongrass (Cymbopogon citratus) by hydrodistillation method in organic and conventional cultivation in the hinterland of Paraíba (Revista Brasileira de Plantas Medicinais, 2020)
The main objective of this work was to evaluate the oil content present in the green leaves of the plant. The method used to extract the essential oil was hydrodistillation, using the crushed green leaves of lemongrass as a sample. The experiment was installed on September 16, 2016 at the IFPB Campus Sousa at the head office, which were cultivated with one plant in each pot with a capacity of 5 kg of organic and conventional fertilizer. After preparing the lemongrass sample, the hydrodistillation process was set up for two hours in a modified Clevenger apparatus. At the end of the distillation, the oil was removed by suction using a glass Pasteur pipette, where the quantification of the essential oil was determined through the ratio of the amount of oil obtained (g) with the amount of fresh leaf (g) used in the extraction and the result was expressed in percentage (%). The results were analyzed by the SISVAR software. Means were compared by Tukey's test at 5% probability. The essential oil (OR) yield of lemongrass submitted to different sources of fertilization showed a significant effect by the Tukey test.